A sequential multistage-targeted nanoparticles for MR imaging and efficient chemo/chemodynamic synergistic therapy of liver cancer. (September 2021) - Wang, Ning; Liu, Chenyu; Yao, Weihe; Wang, Xinmeng; Zhou, Hengjun; Chen, Hailiang; Qiao, Weihong
Highlight: GSH/pH dual-responsive mitochondrial targeting nanoparticles was designed. Integrate ROS burst induced, and MRI function in a single nanoparticles. The nanoparticles realized synergistic CT/CDT therapy with outstanding biosafety. Abstract: The reasonable combination of chemotherapy and chemodynamic therapy has great potential in the treatment of cancer. In this study, a novel multifunctional nanoparticle (CDTLG NPs) with tumor tissue-cell-mitochondria-targeted, tumor-specific drug release and endogenous reactive oxygen species generation are developed for magnetic resonance imaging-guided liver cancer synergistic chemo/chemodynamic therapy. The CDTLG NPs are constructed via self-assembled of glutathione/pH-responsive prodrug, organic chemodynamic therapy agents, and magnetic resonance imaging contrast agents. Through passive targeted, the nanosized CDTLG NPs can accumulate in tumor tissue. After accumulating in hepatoma cells by active targeting, the CDTLG NPs could be destroyed under acidic and reductive intracellular environment to quickly release chemotherapy drugs doxorubicin, camptothecin, and organic chemodynamic therapy agents. Subsequently, due to mitochondrial targeting, organic chemotherapeutic drugs accumulate in the mitochondria of hepatoma cells and generate a large number of reactive oxygen species. The burst of endogenous reactive oxygen species and chemotherapy drugs release achieved synergistic chemo/chemodynamic therapy, which led to more severe cell death than monotherapies. Furthermore, the CDTLG NPs present outstanding in vivo antitumor ability without causing obvious in vivo toxicity. Thus, the study provides an intriguing strategy to chemo/chemodynamic combination therapy-based nanoparticles for enhancing antitumor efficacy. Graphical abstract: Image, graphical abstract